The Staidear Board Game Model Application in Facilitating Vocational School Students Learning - Anak Agung Adi Wiryya Putra; Herman Dwi Surjono (Journal of Education Technology, 2023)
Students need help with learning the basic material of graphic design. It has an impact on low student learning outcomes. This study aims to develop a game-based learning media that can be used to facilitate vocational students' learning in multimedia learning activities. This type of research is research and development using the ADDIE model. The sample in this study was 30 students. Data collection techniques using interviews and questionnaires. Data collection instrument using a questionnaire. Data analysis technique using descriptive analysis. The study's results, namely the material feasibility test, obtained a score of 3.88, while the media feasibility test obtained a score of 3.87. Implementation results 76.6 per cent of respondents are interested in learning multimedia using the Staidear board game, 93.3 per cent of respondents think the Staidear board game is easy to use. It was concluded that board game learning media is appropriate for use in the learning process of graphic design. The application of board game media is effective in learning graphic design. The unique appearance of board games can attract students' interest in learning. Implementing this board game implies an increase in the average student test scores.